Impact of preoperative bowel preparation methods on anastomotic leakage and intestinal motility recovery in laparoscope-assisted heart-shaped anastomosis - Zhang, Pei; Wei, Decheng; Bian, Jian; Qi, Shijin (Frontiers in Surgery, 2025)
BackgroundHirschsprung’s disease (HSCR) is a congenital bowel-obstructive disorder caused by the absence of enteric ganglion cells. While laparoscope-assisted heart-shaped anastomosis (LHSA) shows promise in surgical management, risks like anastomotic leakage persist. Preoperative bowel preparation is key in optimizing surgery outcomes. This study evaluates the efficacy of mechanical bowel preparation (MBP) vs. MBP combined with oral antibiotics (OA) in reducing postoperative complications and improving recovery.MethodsThis retrospective cohort study involved 215 HSCR patients who underwent LHSA between June 2010 and June 2023. Patients were divided into two groups: MBP + OA and MBP alone. Outcomes measured included anastomotic leakage, surgical site infections (SSIs), postoperative intestinal motility, inflammatory markers, postoperative recovery markers, and quality of life assessments.ResultsThe OA + MBP group demonstrated a significant reduction in SSIs (2.65% vs. 9.80%, P = 0.028) and shorter postoperative LOS (4.20 ± 1.20 days vs. 4.80 ± 1.58 days, P = 0.002). Time to first stool (2.16 ± 0.71 days vs. 2.25 ± 0.72 days, P = 0.004) and full feeds (4.18 ± 1.34 days vs. 4.58 ± 1.36 days, P = 0.029) were improved in the OA + MBP group. On the fifth postoperative day, CRP levels were lower in the OA + MBP group (60.1 ± 19.7 mg/L vs. 67.4 ± 22.5 mg/L, P = 0.012).ConclusionThe addition of oral antibiotics to mechanical bowel preparation significantly decreases the risk of SSIs, enhances recovery, and improves both inflammatory profiles and bowel function in LHSA.